Comparative efficacy of an optimal exam between ultrasound versus abbreviated MRI for HCC screening in NAFLD cirrhosis: A prospective study. Issue 7 (28th February 2022) - Huang, Daniel Q.; Fowler, Kathryn J.; Liau, Joy; Cunha, Guilherme M.; Louie, Ashley L.; An, Julie Y.; Bettencourt, Ricki; Jung, Jinho; Gitto, Zachary; Hernandez, Christie; Lopez, Scarlett J.; Gupta, Hersh; et al.
Summary: Background: Retrospective studies report that visualisation of the liver may be severely limited using ultrasound (US), potentially contributing to diminished sensitivity for detection of hepatocellular carcinoma (HCC) among patients with nonalcoholic fatty liver disease (NAFLD) and cirrhosis, but there are limited prospective data. Aims: To compare liver visualisation scores prospectively for US and abbreviated hepatobiliary phase (HBP) magnetic resonance imaging (AMRI) in a cohort of participants with NAFLD cirrhosis and a clinical indication for HCC surveillance. Methods: This prospective multicenter study included 54 consecutive participants (67% women) with NAFLD cirrhosis who underwent contemporaneous US as well as HBP‐AMRI with gadoxetic acid. Primary outcome was the proportion of imaging examinations with severe limitations in liver visualisation (visualisation score C) compared head‐to‐head between US and AMRI. Results: The mean (± standard deviation) age was 63.3 years (±8.4) and body mass index was 32.0 kg/m 2 (±6.0). Nineteen participants (35%) had severe visualisation limitations on US, compared with 10 (19%) with AMRI, p < 0.0001. Nine (17%) participants had <90% of the liver visualised on US, compared with only 1 (2%) participant with AMRI, p < 0.0001. Obesity was a strong and independent predictor for severe visualisation limitation on US (OR 5.1, CI 1.1–23.1, p = 0.03), after adjustment for age, sex and ethnicity. Conclusion: More than one‐third of participants with NAFLD cirrhosis had severe visualisation limitations on US for HCC screening, compared with one‐sixth on AMRI. US adequacy should be reported in all clinical studies and when suboptimal then AMRI may be considered for HCC screening. Abstract : Retrospective studies suggest that abbreviated magnetic resonance imaging (AMRI) provides adequate liver visualization more frequently than ultrasound (US), but a prospective, head‐to‐head comparative study is lacking. We conducted a prospective, multicenter study of US versus AMRI performed head‐to‐head for hepatocellular carcinoma screening among well characterized patients with NAFLD cirrhosis. Our study demonstrates that more than a third of patients with NAFLD cirrhosis have severe visualization limitations on US but only one‐sixth have severe visualization limitations on AMRI.